Insights in laparoscopic surgery of mucinous cystic neoplasm of the liver - Vennarecci, Giovanni; Guglielmo, Nicola; Ettorre, Giuseppe Maria (Laparoscopic Surgery, 2018)
The case report (with video) by Smerieri et al. (1) of Surgical Endoscopy, concerning the laparoscopic surgical treatment of a hepatic mucinous cystic neoplasm (MCN-H), it lends itself to numerous interesting reflections.